Process transfer of PECVD gas barrier coatings between PE-HD and PP hollow bodies (2024)
This study investigates the plasma enhanced chemical vapor deposition (PECVD) coating process transfer between PE and PP substrates. An inverse relationship is observed between the barrier improvement factor (BIF) and applied energy density (E), with PE showing a stronger response. The same process gas ratio optimizes both materials, suggesting geometry influences the barrier effect more than material. However, the barrier on PP is limited, indicating poorer compatibility to functionalization. The development of the intermediate layer did not improve the barrier performance. FESEM analyses and scratch tests suggest material damage during coating application. Further research is needed to optimize the coating process.